What Is Good Writing? Proceedings of a Conference at the University of Connecticut (Storrs, Connecticut, December 6, 1980) - Connecticut Univ., Storrs. Dept. of English; Sheidley, William E.; Connecticut Univ., Storrs. Dept. of English ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
The focus of the conference proceedings in this booklet was evaluation of student writing at various levels and in various fields. The booklet contains a schedule of activities; a description of the morning session, which included a panel discussion on evaluating writing in college freshman composition courses; examples of students' papers, with evaluators' ratings; the full text of the luncheon address, "A Short Long View of Freshman Composition" by Sylvan Barnet; and outlines of the four afternoon workshops: "Writing for Science" by Anthony Phillpotts and Raymond Joesten, "Writing for Business" by Jean Smith, Robin Ray, and Madelyn Vozzola, "Writing for History" by R. Kent Newmyer, and "Writing for the Social Sciences" by Jack Thaw. (EL)
Availability: Connecticut Writing Project, Department of English (U-25), University of Connecticut, Storrs, CT 06268 ($2.00).
ERIC Note: Prepared through Connecticut Writing Project.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Freshmen; Content Area Writing; Higher Education; Writing (Composition); Writing Evaluation; Writing Instruction; Writing Processes; Writing Skills; Collected Works, Proceedings